2019
DOI: 10.3389/fmicb.2018.03299
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Metabolome and Bacterial Community in Whole Crop Corn Silage by Inoculating Homofermentative Lactobacillus plantarum and Heterofermentative Lactobacillus buchneri

Abstract: The present study investigated the species level based microbial community and metabolome in corn silage inoculated with or without homofermentative Lactobacillus plantarum and heterofermentative Lactobacillus buchneri using the PacBio SMRT Sequencing and time-of-flight mass spectrometry (GC-TOF/MS). Chopped whole crop corn was treated with (1) deionized water (control), (2) Lactobacillus plantarum, or (3) Lactobacillus buchneri. The chopped whole crop corn was ensiled in vacuum-sealed polyethylene bags contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
152
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(178 citation statements)
references
References 46 publications
14
152
1
Order By: Relevance
“…The bacterial community was usually dominated by Lactobacillus in well-fermented silages (Hao et al, 2018;Xu et al, 2018;Yan et al, 2019). It is well established that Lactobacillus plays a critical role in silage fermentation by producing LA, reducing pH, and decreasing the relative abundance of undesirable bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial community was usually dominated by Lactobacillus in well-fermented silages (Hao et al, 2018;Xu et al, 2018;Yan et al, 2019). It is well established that Lactobacillus plays a critical role in silage fermentation by producing LA, reducing pH, and decreasing the relative abundance of undesirable bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, until now, limited studies have been reported on PLA. Most of the reports analyzed gramineae silage [27], and the PLA was positively related to the abundance of L. acetotolerans in whole-crop corn silage [20]. In this work, the PLA content was related to the content of NH 3 -N, indicating that the PLA produced during alfalfa ensiling was different from that produced during corn ensiling.…”
Section: Discussionmentioning
confidence: 60%
“…Xu et al found PLA and other metabolites with bacteriostatic activity in whole-crop corn silage, but the treatments had no significant effect on the metabolites [20]. The PLA content was recorded in frozen, grass-dominated crop silages inoculated with LAB [27].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations